Compassion focused group therapy for university counseling centers : a clinician's guide - Cattani, Kara (New York, NY : Routledge, 2022)
"Compassion-focused therapy (CFT) articulates an approach that faces suffering head-on to understand, alleviate, and prevent suffering in ourselves and in others. Compassion Focused Group Therapy for University Counseling Centers is a one-of-a-kind 12-session manual for conducting compassion-focused group therapy on university campuses with students presenting a diverse set of complex mental health concerns. Beginning with suggested readings designed to enrich understanding of the principles covered, each module presents psychoeducation interventions, engaging intrapersonal and interpersonal exercises, and process-oriented instructions. Modules can be followed session-by-session or adapted according to the needs of the group. Eye-catching handouts are included at the end of the modules to help leaders provide visual representation of the themes discussed in each session. This manual is designed to be used by licensed clinicians and should be used in conjunction with the manual's companion Compassion Focused Therapy Participant Workbook which provides clients with summaries of each session, handouts, and key exercises"--
Includes index.
Keywords: College students -- Mental health services; Emotion-focused therapy; Compassion; PSYCHOLOGY / Psychotherapy / Group